Breast atypia: timing of progression to subsequent clinically significant event - Tjoe, Judy A; Singh, Maharaj; Last, Brittany S; Neitzl, Gary F; Marx, J J; Jewett, C (Advocate Aurora Health Institutional Repository, 2014)
Background/significance: Atypical hyperplasia (AH) increases a woman’s risk for breast cancer. This can cause significant anxiety, leading women to choose risk reduction options of tamoxifen and/ or prophylactic mastectomies. Purpose: Understanding the natural history of AH and subsequent breast cancer may help patients select and time options for risk reduction. Methods: Aurora Health Care’s experience was retrospectively reviewed for women initially diagnosed with pure breast AH, either atypical ductal hyperplasia (ADH) and/or atypical lobular hyperplasia (ALH). 31,921 patients with the ICD-9 code of 610.8/.9 (other specified or unspecified benign breast disorder) were screened between 1/1995-12/2010. After elimination of repetitive diagnoses from multiple visits, non-breast disease, non-atypical benign breast disease, and previous diagnosis of breast malignancy, the study cohort consisted of 370 breasts with a principal diagnosis of pure AH involving 360 patients. Slides were reviewed by a single pathologist, blinded to the original diagnosis. Those patients who progressed to a subsequent clinically significant event (SCSE), i.e., another diagnosis of AH (increasing the calculated Gail Model 5-year and lifetime risk of breast cancer) or malignancy were analyzed for race, age, SCSE pathology, laterality, medical/surgical risk intervention, and time to progression. Results: 31(8.61%) patients developed a SCSE. Mean age at initial diagnosis of AH was 57.9 years (SD 10.6, range 29-84). Racial makeup was similar to controls: 27 (87.1%) Whites, 3 (9.6%) Blacks. 18 (58.1%) developed the SCSE within the ipsilateral breast, and 13 (41.9%) within the contralateral breast (p=0.369) whether the initial diagnosis was ADH, ALH, or mixed (p=0.405). Regarding histology of the 2nd event, 14 (45.2%) were diagnosed again with AH, 5 (16.1%) progressed to carcinoma in situ (CIS), and 12 (38.7%) progressed to invasive carcinoma (IC) (p=0.115). Resection of the AH did not reduce the chance of SCSE within the ipsilateral breast ...